2021
DOI: 10.1002/smtd.202101276
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Chemistry and Interface Engineering of Hydrogel Electrolyte to Strengthen Durability of Solid‐State Zn–Air Batteries

Abstract: Famous for high theoretical energy density (≈1086 Wh kg −1 ), five time that of dominant lithium ion batteries (LIBs), the recently developed flexible solid-state Zn-air batteries (FSZABs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…For example, the work by Wang et al 42 reported a maximum power output of 231 mW cm −2 for a ZAB with an aqueous alkaline electrolyte, however, this cell had a stable charge/discharge performance for only 25 h. The use of micron-scale CFs in this work generated a porous 3D design for the air electrode with a maximum power output of 240 mW cm −2 and stable cycling behavior. This power output is rare for ZABs and the cycling behavior of MnCo 2 O 4 / CF-Hydrogel-30-mM was the same or better than the batteries (with GPEs) reported by Roy et al, 31 Tang et al, 43 Miao et al, 30 Chen et al, 29 Ramakrishnan et al, 44 Muthurasu et al 45 and Chen et al, 46 even though those studies used lower current densities and/or shorter cycling durations for battery cycle testing. For example, the batteries reported by He et al 47 and Tran et al, 48 using PAA as the GPE, have relatively high maximum power densities of 158 and 146 mW cm −2 , respectively.…”
Section: Fullsupporting
confidence: 68%
“…For example, the work by Wang et al 42 reported a maximum power output of 231 mW cm −2 for a ZAB with an aqueous alkaline electrolyte, however, this cell had a stable charge/discharge performance for only 25 h. The use of micron-scale CFs in this work generated a porous 3D design for the air electrode with a maximum power output of 240 mW cm −2 and stable cycling behavior. This power output is rare for ZABs and the cycling behavior of MnCo 2 O 4 / CF-Hydrogel-30-mM was the same or better than the batteries (with GPEs) reported by Roy et al, 31 Tang et al, 43 Miao et al, 30 Chen et al, 29 Ramakrishnan et al, 44 Muthurasu et al 45 and Chen et al, 46 even though those studies used lower current densities and/or shorter cycling durations for battery cycle testing. For example, the batteries reported by He et al 47 and Tran et al, 48 using PAA as the GPE, have relatively high maximum power densities of 158 and 146 mW cm −2 , respectively.…”
Section: Fullsupporting
confidence: 68%
“…[43,44] In virtue of this advantage, strong interfacial bonding between PASHE and electrodes can be formed, which leads to a decreased interfacial charge resistance and eventually facilitates interfacial reaction kinetics. [45] Consequently, the satisfying mechanical performance and adhesive capability guarantee the adaptability and stable energy output at deformations for ZHMSCs with PASHE.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 However, the inevitable strain mismatch arising from the incompatible mechanical properties between the rigid material and exible substrate would result in detachment and aggregation of the electrode material under repeated mechanical deformation. [24][25][26][27] In addition, currently most solid-state exible supercapacitors are assembled by physically compressing layered electrodes together with the electrolyte, 28 which usually lacks adhesion force, especially for high-water-content hydrogels. 29,30 As a consequence, two neighboring components are prone to express undesirable displacement or detachment under repeated mechanical deformation, and the poor interfacial contact at the interface between the electrolyte and the electrodes inevitably results in cell death.…”
Section: Introductionmentioning
confidence: 99%